Multimedia applications of digital information technologies and their impact - A'zamov Bunyodjon Mirzohid oglu (Genius Journals, 2025)
This article analyzes the role and impact of digital information technologies in multimedia applications. Digital information technologies create new possibilities for presenting information by using video, audio, and text together. Multimedia applications play an important role in improving the user experience in areas such as education, marketing, and healthcare. The article also examines future trends and social impacts. As a result, the importance of digital information technologies and multimedia technologies in modern society is emphasized, as well as the need for careful use
Keywords: Digital information technologies; multimedia applications